Agrarian change through speculation: Rural elites as land brokers for mining in Colombia - Kristina Dietz (Journal of Agrarian Change, 2023)
This paper studies the connections between the expansion of mining capital, speculative forms of land grabbing and agrarian transformation. It is argued that in periods of commodity boom, the landowning rural elite benefits from mining through speculative land deals with mining companies. They act as `land brokers' for the mining firms, helping them to overcome a significant barrier to land accumulation through the de facto abolition of landed property. The analysis is based on a qualitative case study on the expansion of coal mining in central Cesar in northern Colombia. To develop my arguments, I refer to the concept of accumulation by dispossession as defined by Michael Levien, and historical materialist approaches on rent, and speculative land dispossession. In addition, I use concepts developed for studying coercive land grabbing and agrarian elite participation in armed conflicts to analyse the mechanisms applied to (coercively) acquire rights to land. It is concluded that with high global prices for minerals, metals and fossil fuels, the expansion of mining in the countryside fosters a process of agrarian change through land speculation that is articulated in a reconcentration of landed property, a re-strengthening of the rural landowning elite and the dissolution of peasant agriculture.
Keywords: 630; accumulation by dispossession; agrarian transformation; Colombia; land brokering; mining; rural elite; speculation